Molecular docking study of hyaluronic acid against interleukin-6 (7DC8 protein) in COVID-19 patients with periodontitis - Ismail, Ade; Aulia Azhar, Syafirudin (IIUM Journal of Orofacial and Health Sciences, 2023)
Coronavirus disease 2019 (COVID-19) is a new disease caused by a coronavirus, namely SARS-CoV-2. This virus was entered inside the host by angiotensin-converting enzyme receptors (ACE2). Recent evidence suggests that sulcus fluid in the periodontal pockets of patients with periodontitis may be a source of SARS-CoV-2 and a potential reservoir for increasing oral viral load in patients with confirmed COVID-19. ACE-2 is expressed in stratified squamous epithelium mainly on the dorsal tongue and gingiva. The gingival sulcular epithelium is the entry point for SARS-CoV-2 into the periodontal pocket epithelium through the gingival crevicular fluid (GCF). Hyaluronic acid (HA) is a high molecule of heavy polysaccharide (glycosaminoglycan) which has several functions, such as anti-inflammatory and accelerated wound healing. It could decrease the levels of several cytokines. This study aims to analyze the interaction of HA against the IL-6 coronavirus receptor in periodontitis through a molecular docking study using MOE 2015.10 software with IL-6 receptor (7DC8) as the protein model to predict the binding of HA with 10 poses. The 7DC8 protein was prepared by adding charge and the validation method was performed with RMSD <2Å which indicates this method is valid. The results of this study showed that there are interaction between HA and the IL-6 receptor via amino acid residue interaction at the Leucine 98 (bond energy -0.7 kcal/mol), Serine 52 (bond energy -1.7 kcal/mol), Glycine 53 (bond energy -1.5 kcal/mol), and Glycine 299 (bond energy -1.6 kcal/mol). HA has an interaction with coronavirus at the IL-6 receptor of periodontitis based on molecular docking study and can potentially be used as a therapeutic option in COVID-19 with periodontitis. In conclusion, hyaluronic acid has the potential as an anti-inflammatory drug of choice in COVID-19 patients with periodontitis.